The Effects of Board Games Learning Provision on Self-Management Skills of Young Children - Masang, Marisa; Butkatunyoo, Oraphan (Interdisciplinary Academic and Research Journal, 2023)
Choosing a way to encourage children with games should have characteristics that encourage children to practice thinking, memory, planning, practicing problem-solving, and using various strategies, including predicting the outcome that will occur in play, imagination also helps children develop emotional management. Board games are games that create interaction with friends or players, and must use strategies or strategies to help them win, board games have specific styles for each game differently. The purpose of this study was to study the effects of board game learning provision on the self-management skills of young children and observe behavior that shows skill in Self-management. The target group in this study was 4 - 5 years old who were studying in the kindergarten 2ndyear semester 2 in the academic year 2022 at Ramkhamhaeng University Demonstration School (elementary level), Bangkok. One classroom has 30 children by purposive sampling. The instruments used in this study included. 1 Lesson plan of board learning provision for developing self-management has a totally of 24 plans 2 Snakes and ladders for developing self-management and 3 Self-management skills behavior of young children observation form. Data by analysis, mean, standard division, and content analysis. The study results of the study revealed that organizing a learning experience for board games can develop self-management skills in early childhood children by finding that early childhood children who have been organized to experience learning board games to develop self-management skills Overall, all 30 children had change in self-management behavior and higher scores each time, with the 1st time having an average score of 0.26 and the 24th time having an average score of 1.65, which were progressive and higher respectively the average score of self-management skills of young children was higher, there were changes and development in all 4 aspects. Emotion regulation the 1st time had an average score of 0.30, and the 24th time had an average score of 1.68. Goal setting the 1st time had an average score of 0.20, and the 24th time had an average score of 1.66. Flexible thinking the 1st time had an average score of 0.30, the 24th time had an average score of 1.58, and self-discipline the 1st time self-discipline had an average score of 0.25, the 24th time. with an average score of 1.67. The aspect with the highest average score followed by emotion regulation. Goal setting with self-discipline and flexible thinking respectively.